Evaluation Of the Influence of Good Corporate Governance On The Level of Financial Health of PT Telkom Indonesia TBK For The Period 2019 – 2023 - Tarigan, Wico Jontarudi; Purba, Djuli Sjafei; Purba, Desmi Triyanti (Jurnal Ilmiah Accusi, 2025)
Study This aiming for analyze the influence of Good Corporate Governance (GCG) on health finance of PT. Telkom Indonesia Tbk during period 2019 to 2023. Variables independent used​ covering size of the board of commissioners, size directors, and audit committee, while variable dependent is indicator health finance in the form of Return on Assets (ROA) and Return on Equity (ROE). Method research used​ is quantitative with approach multiple linear regression analyzed​ use device SPSS software. Data used is secondary data obtained​ from report finance PT. Telkom Indonesia Tbk's annual report published in a way officially on the Indonesia Stock Exchange (IDX). The results of the analysis show that in a way simultaneous GCG variables have an effect on ROA, but No significant towards ROE. In partial, size board of directors own influence positive significant on ROA, whereas the size of the board of commissioners and audit committee is not show influence significant to second indicator finance. This indicates that effectiveness of governance companies, in particular role directors, contributing to the improvement health finance company. Implications from study This important for management of state-owned enterprises in increase transparency, accountability and performance finance through implementation principles of effective GCG. Research This also provides recommendation for investors and stakeholders interest for consider governance aspects​ in taking decision investment and supervision company